Edentulousness and complete denture care in the Western Cape Province with specific reference to the need for and feasibility of establishing denturists as a new occupational category in the oral health care work force - Hartshorne, Johannes Enoch (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1998.